Ação do glifosato nos parâmetros fotossintéticos do guaranazeiro - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
In many crops, the underdoses of herbicides deposited in a drift culture, are suspected of altering their photosynthetic mechanisms. Due to the need of weed management in guarana crop, this work aims to evaluate the effect of low doses of the herbicide glyphosate in the photosynthetic apparatus guaranazeiro seeddlings. Seedlings of the cultivars BRS-Andirá and BRS-Maués were submitted to underdoses of 0; 324 g and 432 g of the recommended glyphosate. These effects were evaluated in day two days and seven days after the aplication. The effects of glyphosate were performed through on gas exchange analysis, chlorophyll fluorescence and chlorophyll content index (ICC). All parameters for gas exchange were significant for the underdose factor. The chlorophyll fluorescence parameter was not significant for any of the factors and the ICC was significant in all factors and interactions of these factors. The dose of 324 g i.a. ha- 1reduced the rates of all parameters for gas exchange while the higher dose was not different from the control. The ICC for BRS-Andirá had its values reduced with the increase of glyphosate subdoses, while BRS-Maués had its values reduced when submitted the dose 324 g i.a ha-1 but at 432 g i.a ha- 1 increased the rates. On the seventh day of evaluation the ICC for the BRS-Andirá was reduced, while for the BRS-Maués were lifted. The guarana seedlings they underwent changes in their gas exchange when subjected to glyphosate underdoses, but their effects did not persist. The ICC was useful in observing the effect of low doses of glyphosate on guarana seedlings.
Keywords: Paullinia cupana (guaranazeiro); Herbicida; Trocas gasosas; CIÊNCIAS AGRÁRIAS: AGRONOMIA